10 Effects of Eupatorium adenophorum (flavonoids) in the rat model of benign prostatic hyperplasia. (19th December 2016) - Miao, Mingsan; Wang, Tan; Liu, Jing; Guo, Lin
Abstract : Objectives: This study investigated the effect of total flavonoids on benign prostatic hyperplasia (BPH) rats though the administration of Lycopus decoction and Eupatorium adenophorum . Methods: Ninety male Wistar rats, weighing 280–300 g, received an intraperitoneal injection of hydrazine hydrate, and the testes were removed bilaterally. Another 10 rats underwent a sham operation. Intramuscular injections of penicillin 200 000 units/kg were given. The rats were randomly and evenly divided into a control group, model group, Longbishu group, large, medium and small doses of Lycopus decoction groups, and large, medium and small doses of E. adenophorum flavonoids groups. On the 8th day after castration, rats were injected with testosterone propionate 4 mg/kg/day and irrigated with large, medium and small water decoctions of E. adenophorum (4 g/kg, 2 g/kg and 1 g/kg, 0.2 mL/100 g), large, medium and small doses of total E. adenophorum flavonoids (400 mg/kg, 200 mg/kg and 100 mg/kg, 0.2 mL/100 g) and Longbishu capsule suspension (300 mg/kg, 0.2 mL/100 g). The model group and blank control group were given the same volume of normal saline, continuing for 30 days. Then 2 hours after the last administration, the rats were weighed and euthanized. Prostate tissue was removed, the wet weight was measured, and the prostate index was calculated. Testosterone and oestradiol levels in prostate homogenate, and the levels of bFGF, TGF-β1, IGF-I and EGF were determined. Other samples of prostate tissue were fixed in formalin solution, and cytological morphology was examined under a light microscope. Results: E. adenophorum water decoction and total flavonoids significantly reduced the rat prostate index, decreased serum testosterone levels, increased serum oestradiol levels, decreased bFGF, EGF and IGF levels in the rat prostate, elevated TGF-β1 levels, reduced rat prostate density, and increased the specific surface area. Conclusions: The results of this study showed that treatment of benign prostatic hyperplasia (BPH) had a good effect and suggest a new therapy for BPH. Acknowledgments: This research was financially supported by the Henan University of Chinese Medicine Graduate Student Innovation Fund (Grant No. 2014YCX011) and Research Topics of Traditional Chinese Medicine in Henan Province (Grant No. 2014ZY02007).